Spatial correlation of water distribution and fine structure of arabinoxylans in the developing wheat grain. (15th October 2022) - Fanuel, Mathieu; Grélard, Florent; Foucat, Loïc; Alvarado, Camille; Arnaud, Bastien; Chateigner-Boutin, Anne-Laure; Saulnier, Luc; Legland, David; Rogniaux, Hélène
Abstract: This study was to investigate the distribution of water and arabinoxylan structures in growing wheat grain using two complementary imaging techniques, magnetic resonance microimaging (μMRI) and mass spectrometry imaging (MSI). μMRI showed an inhomogeneous water distribution, particularly at early stages. This heterogeneity revealed histological differences that corresponded, within the limits of resolution of μMRI, to tissues with specific physiological functions, including the vascular bundles, the cavity and the endosperm periphery. All of these tissues had a higher water content than the central endosperm. MSI revealed distinct xylan structures in these regions with high levels of Ara f substitution around the cavity and acetylated xylans concentrated at the endosperm periphery. For the first time, acetylation and Ara f substitution of arabinoxylans were found by image processing to spatially correlate with water distribution in planta . Acetylation and Ara f substitution of xylans, which alter chain-chain interactions and increase wall porosity, decreased as the grain matured. Graphical abstract: Unlabelled Image